2019
DOI: 10.1002/adsu.201900065
|View full text |Cite
|
Sign up to set email alerts
|

Mechano‐Fenton–Piranha Oxidation of Carbon Nanotubes for Energy Application

Abstract: Emission of nitrogen oxides (NOx) from chemical processing of materials is a serious environmental concern, frustrating the development of many innovative technologies. For example, sulfonitric oxidation is the most widely used method for processing carbon nanotubes (CNTs), producing a large amount of NOx. As a result, large scale applications of CNTs for downstream purposes remain challenging. Herein, a NOx‐free oxidation method is proposed for CNTs processing. It starts with mechanically grinding, and then o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Apparently, all the TiO x -Ti 3 C 2 /S, VO x -V 2 C/S, and NbO x -Nb 2 C/S display suppressed semicircles in comparison with SP/S electrode, indicative of declined charge transfer resistances and boosted reaction kinetics (Figure S18). 36,43,46,48,49 The smaller equivalent series resistances of MO x -MXene/S further imply high electrical conductivity of MO x -MXene, agreeing well with the theoretical simulation. Moreover, the slopes of plots in the low-frequency region for MO x -MXene/S are steeper than that of SP/S, suggesting faster charge diffusion that is consistent with the foregoing analysis.…”
Section: Resultssupporting
confidence: 85%
“…Apparently, all the TiO x -Ti 3 C 2 /S, VO x -V 2 C/S, and NbO x -Nb 2 C/S display suppressed semicircles in comparison with SP/S electrode, indicative of declined charge transfer resistances and boosted reaction kinetics (Figure S18). 36,43,46,48,49 The smaller equivalent series resistances of MO x -MXene/S further imply high electrical conductivity of MO x -MXene, agreeing well with the theoretical simulation. Moreover, the slopes of plots in the low-frequency region for MO x -MXene/S are steeper than that of SP/S, suggesting faster charge diffusion that is consistent with the foregoing analysis.…”
Section: Resultssupporting
confidence: 85%
“…The LSV curves in Figure S19 indicate that the ORR activity is enhanced with the increased value of E 1/2 when the milling time rises from 1 to 3 h. However, the value of E 1/2 drops when the ball milling time is further increased to 5 h; detailed results can be seen in Table S5. The SEM images (Figures S20 and S21) and EIS results (Figure S22) indicated that the excessive milling speed or time tends to induce the formation of aggregates, consequently leading to the reduced active area and degraded electrocatalytic performance. , Therefore, the appropriate milling speed and time were respectively set as 1200 rpm and 3 h in this work. The ORR performance of catalysts with lower iron content have been prepared without acid etching in this work (Figure S23); the result shows that too low iron content in the precursors results in an insufficient density of Fe–N 4 sites, leading to the poor ORR performance .…”
Section: Resultsmentioning
confidence: 99%
“…There is a possibility of chemical modification by mixtures of hydrogen peroxide with different salts, such as the Fenton's reagent (H2O2/FeSO4). Prolonged treatment with such a mixture leads to the formation of hydroxyl groups only [25].…”
Section: Theorymentioning
confidence: 99%